Centralising a counter public: an ethnographic study of the interpretation of mainstream news media by young adults in Joza - Ponono, Mvuzo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
The 2014 national general elections were characterised by a cloud of scandal hanging over the ANC, and the ANC president Jacob Zuma. The biggest and darkest cloud was the Nkandla scandal. Owing to a reported R246 million spent by the state to refurbish his private home, the president stood accused of wasteful expenditure and financial irregularity. In a country reeling from the continued effects of apartheid, which include high unemployment and poverty, the scandal was a bombshell. According to a vocal and often adversarial mainstream media sphere, the ANC went into those elections with an albatross around its neck. The dominant thought was that the ruling party would suffer a heavy loss of votes. This outcome did not materialise. The ANC lost a marginal share of its previous vote. Mainstream media and civil society were confounded. What had happened? Why had poor black South Africans continued to vote for a party that was obviously in breach of the constitutional order? Against the mismatch between what was predicted or purported and the outcome, this study investigates how young people in the township of Joza, Grahamstown, interpreted one of the biggest political scandals in South Africa's fledgling democracy. Using a combination of subaltern studies, counter public sphere and audience study, the research looks into the interpretation of a mainstream media scandal that was supposed to diminish the chances of the ANC retaining power, but, instead, barely dented its majority. Through a combination of interviews and participant observation, the study found that young people in the township of Joza demonstrated that they chose to ignore the messages about the corruption of the ANC. The data suggests that they did so, not because of overt racial solidarity, but due to the fact that in a context of high inequality, and continued limitations on economic emancipation, the party shone brightly as a vehicle for economic development. Overall, the study argues that the seemingly dubious undertaking to continue with the ANC is a calculated decision that makes sense when viewed within a given socio-economic context.
Keywords: African National Congress Mass media -- Political aspects -- South Africa Press and politics -- South Africa; South Africa -- Politics and government -- 21st century Zuma, Jacob -- Political and social views; Political corruption -- 21st century Elections -- South Africa Voting -- South Africa Misconduct in office -- South Africa Abuse of administrative power -- South Africa Young adults -- Political activity -- South Africa -- Grahamstown Young adults -- Politics and government